THE VICISSITUDES OF MALI’S EMPIRE - Makan Drame, Chaibou Fodie; Othman, Mohammad Redzuan (SEJARAH: Journal of the Department of History, 2017)
This article begins with a discussion of Mali’s great dynasties comprising three main empires: Mali’s Empires, Ghana’s Empires and Songhai Empires. The second part examines how these empires which occupied the Savannah region influenced it with the gold trade, Islamic scholarship and manuscripts. These manuscripts exist in Malian main institutions such as Ali Ahamad Institute in Gao and University of Timbuktu today. The article then examines the empires’ rise and the impact of its fall on the French colonial penetration of Mali in the 1850s. Both developments have an interesting historical setting which this article examine. First, the historical development of Mali’s dynasties; and second, the historical development of French slave trade and colonial agenda in Mali where the foreign regime conspired and forced Malian dynasties to fall. Indeed this factor was considered as reasons for their fall. Different tribes of Mali which existed at the time were in fact the base for the origins of Mali’s empires. In this ancient era, they mainly concentrated on different business interactions and religious activities for national interests and Islam throughout the Savannah, which was much influenced by their trade and transactions for Mali’s economic integration including Islamization of the region.